Optimized resource allocation and trust management schemes for non-orthogonal multiple access on the internet of vehicles. (September 2022) - Singh, Nikhil Kumar; Singh, Rishi Kumar; Khare, Deepak Kumar; yadav, Himashu; Jain, Pranita; Bhatt, Mohammed Wasim
Abstract: This paper considers a vehicle edge computing system that uses nonOrthogonal multiple access technologies for task uploading and data packet downloading to solve the problems of insufficient computing power on the vehicle side, significant task processing delay, high energy consumption, and lack of wireless resources. The study looks into how to develop, compute offloading, and content caching queues under the vehicle edge computer network, with the help of NOMA, to decrease the total energy consumption at the MEC end. Regardless of the fact that there have been a lot of studies on computational offloading and content caching, the energy consumption of both is rarely investigated and dealt with simultaneously. The simulation findings demonstrate that, compared to typical orthogonal multiple access methods, the nonOrthogonal multiple access offload cache approach in the vehicle edge computing system may considerably lower the system energy consumption.